2020
DOI: 10.3389/fnhum.2020.509075
|View full text |Cite
|
Sign up to set email alerts
|

Variance and Scale-Free Properties of Resting-State Blood Oxygenation Level-Dependent Signal After Fear Memory Acquisition and Extinction

Abstract: Recently, the dynamic properties of brain activity rather than its stationary values have attracted more interest in clinical applications. It has been shown that brain signals exhibit scale-free dynamics or long-range temporal correlations (LRTC) that differ between rest and cognitive tasks in healthy controls and clinical groups. Little is known about how fear-inducing tasks may influence dispersion and the LRTC of subsequent resting-state brain activity. In this study, we aimed to explore the changes in the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 67 publications
(107 reference statements)
0
3
0
Order By: Relevance
“…Similarly, Barnes et al ( 2009 ) observed lower LRTC during cognitive performance that was followed by recovery to baseline levels ~15 min after completing the task. These and similar studies have proposed that there are baseline levels of self‐similarity that are temporarily disturbed by active tasks /cognitive effort (Barnes et al, 2009 ; Churchill et al, 2016 ; Tetereva et al, 2020 ; Wenger et al, 2017 ). Other studies have reported that increased LRTC in resting state data is reflective of prior task performance (Mahjoory et al, 2019 ; Samek et al, 2016 ; Wink et al, 2006 ).…”
Section: Introductionmentioning
confidence: 85%
“…Similarly, Barnes et al ( 2009 ) observed lower LRTC during cognitive performance that was followed by recovery to baseline levels ~15 min after completing the task. These and similar studies have proposed that there are baseline levels of self‐similarity that are temporarily disturbed by active tasks /cognitive effort (Barnes et al, 2009 ; Churchill et al, 2016 ; Tetereva et al, 2020 ; Wenger et al, 2017 ). Other studies have reported that increased LRTC in resting state data is reflective of prior task performance (Mahjoory et al, 2019 ; Samek et al, 2016 ; Wink et al, 2006 ).…”
Section: Introductionmentioning
confidence: 85%
“…We analyzed resting-state fMRI data of 23 healthy right-handed volunteers (23.90 ± 3.93 years old, 8 females) who participated in the study of longitudinal changes in the brain RS functional connectivity such as RS after fear learning and fear memory extinction (RS_FE) in comparison with the initial RS data (RS_0). These data were already used in the previous projects 28 .…”
Section: Participants and Proceduresmentioning
confidence: 99%
“…During the RS scanning, participants were asked to remain calm with their eyes closed and to try not to think purposefully. A full description of the experimental procedure can be found in our previous paper 28 . In the current study, we concentrated on analyzing RS1 and RS2 interleaved by FL and FE to separate two RS scan data acquired before and after exposure to emotionally meaningful stimuli.…”
Section: Procedures Descriptionmentioning
confidence: 99%